Development of the Islamic Religious Education Curriculum at PTU as Strengthening Multicultural Islam - Febriyarni, Busra; Asha, Lukman; Fakhruddin, Fakhruddin (Institut Agama Islam Negeri (IAIN) Curup, 2024)
One of the courses in educational institutions in higher education, which is very related with the development of morals and behavior is Religious Education. Islamic Religious Education (PAI) at Public Higher Education (PTU) is a continuation of the teaching received by students starting from the Elementary Level, Junior and Senior High Schools. In the structure of the national higher education curriculum, Islamic religious education courses are compulsory subjects for all Muslim students in all public tertiary institutions, both public and private universities. The progress of an educational institution, one of which is determined by the teaching materials or curriculum applied, whether it is in accordance with the needs of stakeholders. Indonesia is a multicultural country, so the design of teaching materials or curriculum must be developed according to the demands of the times, times and circumstances. Therefore, the authors state that there are 4 reasons why this paper is important to study: First, the lack of knowledge of Islam among PTU students and public schools; second, the rise of brawls between students (students); third, lack of appreciation among students and students in the field of religion; and fourth, the decreased empathy and religiosity of students and students.